Downregulation of HDGF inhibits tumorigenic phenotypes of hypopharyngeal squamous cell carcinoma by suppressing the AKT/mTOR/VEGF pathway - Yang, Feilong; Zhang, Qiang; Shan, Jiahao; Du, Xinyue; Han, Yang; Liu, Ziyang (Frontiers in Oncology, 2025)
BackgroundHypopharyngeal squamous cell carcinoma (HSCC), an aggressive HNSCC subtype characterized by high metastatic potential and poor prognosis, frequently overexpresses hepatoma-derived growth factor (HDGF), a factor implicated in tumor progression. This study investigates the functional role of HDGF in HSCC and its regulatory mechanisms involving epithelial-mesenchymal transition (EMT) and the AKT/mTOR/VEGF signaling pathway.MethodsBioinformatic analysis of TCGA data revealed elevated HDGF expression in HSCC tissues, significantly correlating with clinical stage. HDGF expression was depleted in the FaDu HSCC cell line using siRNA. Cell proliferation, migration, and invasion were assessed using CCK-8, wound healing, and Transwell assays, respectively. Western blotting evaluated changes in EMT markers (E-cadherin, N-cadherin, Snail, Slug) and key components of the AKT/mTOR/VEGF pathway (p-AKT, p-mTOR, VEGFA).ResultsBioinformatics analysis confirmed HDGF overexpression across HNSCC subtypes. In FaDu HSCC cells, siRNA-mediated HDGF knockdown significantly attenuated proliferation, migration, and invasion. Mechanistically, HDGF depletion reversed EMT progression, evidenced by E-cadherin upregulation and concurrent N-cadherin, Snail, and Slug downregulation. Western blotting demonstrated that HDGF knockdown suppressed AKT/mTOR signaling, as indicated by reduced p-AKT and p-mTOR levels, and decreased VEGFA expression.ConclusionOur findings establish HDGF as a key promoter of HSCC progression through dual regulation of EMT and AKT/mTOR/VEGF pathways, suggesting its potential as a therapeutic target. These results provide mechanistic insights for developing HDGF-targeted strategies against this lethal malignancy, warranting further clinical exploration.